Manufacturing of joints of stainless steels through microwave hybrid heating. (2018) - Pal, Mainak; Sehgal, Shankar; Kumar, Harmesh; Pal Singh, Amrinder
Abstract: This paper presents a review of stainless steel material joints manufactured through the microwave hybrid heating technique instead of normally used conventional or other non-conventional welding methods. Starting with a tutorial introduction of the microwave joining process and its applications, the paper reviews the work done by various researchers in the field of microwave joining especially targeting the joints that involved stainless steel as at least one of the specimen to be joined through microwave hybrid heating. Main emphasis has been laid only on stainless steel joints because of their wider application in industry instead of other alloys which can be joined through microwave joining technique. Current issues with microwave joining technique and future directions for research work have also been presented and discussed.